KEANEKARAGAMAN DAN KELIMPAHAN SUMBERDAYA IKAN DI TELUK KLABAT, PERAIRAN BANGKA BELITUNG [Diversity and abundance of fishes resources in Klabat Bay, Bangka Belitung Seas] - Frensly D. Hukom (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2010)
A research on reef fishes was done in June-July 2003. The research aims to describe composition, distribution, abundance of species, and community structure of fish. Research was executed using visual census method at five stations LIT (Line Intercept Transect) and forty stations RRA (Rapid Reef Assesment). Sample fish was caught using beach net at some locations. Research recorded successfully 108 species of reef fishes which included in 25 genera with 5,211 individuals, in observation area as width as 5,750 m2. Three groups of reef fish that found is a group of major fish, target fish, and indicator fish. Composition of reef fish species was consisted of 36 target fish species (food fish), two indicator fish species, and 70 major fish species. Group of dominant food fish is Caesio cunning, Leiognathus splendens, Scarus gobhan, and Cephalopholis boenack. Two indicator species found is Chaetodon octofasciatus and Chelmon rostratus. The dominant fish in major group are Chromis ternatensis, Abudefduf sexfasciatus, Neopomacentrus anabatoides and Amblyglyphidodon curacao. Abundance of species and number of fish individuals at each station of transect ranges from 6 species to 48 species and 27 individuals to 792 individuals. Fish in Klabat Bay was divided in three groups, namely group of fish found at the front of outer Klabat Bay, group of fish in outer Klabat Bay, and group of fish in inner Klabat Bay.